Adsorption behavior and interfacial dilational properties of asphaltenes at the interface between n-decane/α-methylnaphthalene and brine water. Issue 6 (4th May 2020) - Liu, Daiwei; Li, Chuanxian; Yang, Fei; Sun, Guangyu; You, Jia
Abstract: As the complex component in crude oil, asphaltenes adsorb at the interface and exhibit unique interfacial properties, ruling the emulsifying properties and emulsion stability of produced fluid. Hence, this study deals with the adsorption behavior and interfacial dilational properties of asphaltenes. To investigate the adsorption behavior of asphaltenes, the dynamic interfacial tension is obtained with the pendant drop shape method at various concentrations and temperatures. Based on the adsorption kinetic equation, the adsorption behavior is found to be controlled by different mechanisms at different stages. The initial stage is dominated by the diffusion mechanism. Then, the adsorption process is gradually affected by diffusion and random sequential adsorption simultaneously. Finally, the controlling factor changes to the random sequential adsorption of adsorbed asphaltenes. A higher concentration of asphaltenes can accelerate the diffusion coefficient by increasing the concentration gradient, while the effect of temperature is weaker than concentration. Based on the experimental results, a new method is developed to quantify the influences of different mechanisms. After that, the droplet dilation experiment is carried out to probe the structural properties of the formed interfacial layer. By fitting the experimental data with the Langmuir equation of state, the average interfacial area occupied per asphaltene molecule is calculated. Finally, the emulsion stability experiments are carried out to support the conclusions in the interfacial experiments. This study enriches the adsorption kinetics theory of asphaltenes. It also contributes to the safe and economical transportation of produced fluid and rises the efficiency of demulsification. Graphical Abstract: